2019
DOI: 10.3390/app9050824
|View full text |Cite
|
Sign up to set email alerts
|

A Modeling Framework to Investigate the Influence of Fouling on the Dynamic Characteristics of PID-Controlled Heat Exchangers and Their Networks

Abstract: The present work is an extension of the authors’ previous research, where changes in the dynamic behavior of heat exchangers induced by fouling build-up were studied. In the present work, the authors used the previously elaborated and validated mathematical model of transient heat exchange with the influence of thermal resistance of fouling taken into account. The behavior of specific Heat Exchanger Networks (HENs) coupled with a Crude Distillation Unit together with their control loops is simulated using Simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The prediction model uses the present input and past output to generate future outputs. A prediction model with dynamically varying model parameters converts the conventional MPC to its adaptive variant 16,33 . In the proposed work, the LPV model is used to vary the model parameters concerning the FR as in ().…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prediction model uses the present input and past output to generate future outputs. A prediction model with dynamically varying model parameters converts the conventional MPC to its adaptive variant 16,33 . In the proposed work, the LPV model is used to vary the model parameters concerning the FR as in ().…”
Section: Methodsmentioning
confidence: 99%
“…A prediction model with dynamically varying model parameters converts the conventional MPC to its adaptive variant. 16,33 In the proposed work, the LPV model is used to vary the model parameters concerning the FR as in (8). The LPV models are defined in the statespace form with A, B, C corresponding to the state, input, and output matrix, which governs the dynamics of HE.…”
Section: Design Of Adaptive Mpcmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic characteristics of the PID controller were considered by Trafczynski et al (2019a). The authors concluded that periodic and systematic adjustment of the optimal values of PID gains can prevent the adverse effect of fouling and minimize the effect of interacting heat exchangers.…”
Section: Introductionmentioning
confidence: 99%